IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH PADA ASPEK PERAN SERTA MASYARAKAT DI SEKOLAH MENENGAH ATAS NEGERI 1 PADANG - Dita Novelina Risno (Universitas Negeri Padang, 2015)
This research aims to determine how the implementation of school based management on aspects of community participation in SMA Negeri 1 Padang. Research includes a research descriptive with a population of 66 people. This research didn’t use the sample, but all respondents to the research population. The research instrument was a questionnaire in the form of Likert scale. The results indicate implementation of school based management on aspects of community participation in SMA Negeri 1 Padang in good categories with an average score of 4,2.Keyword: School based management and Community participation